When the Source Country Becomes the Host Country: International Students' Motivations for Studying in China - Chrystal, Joanne (Auckland University of Technology, 2020)
Currently over five million students migrate overseas to complete their tertiary education. With more than 50 countries vying for international students and the number of mobile students expected to increase to 8 million by 2025, the international education industry is extremely competitive. As China is the largest source country of international students in the world, international education scholarship has focused on exploring the unidirectional, vertical flow of Eastern students, particularly students from China, studying in Western, English-speaking countries. Despite China’s rise to become one of the leading host countries of international students, little research has investigated the reverse flow of students selecting an Eastern country, specifically China, as a study destination. Existing literature depicts the decision to study overseas as a high-risk, research extensive decision-making process, which requires host destinations to provide a wealth of information in order to feature in students’ consideration set. Students are influenced by various push-pull factors, interpersonal sources and information sources. Previous research has shown that the pull factors which attract students from developing countries to study in a developed country include the country’s reputation, the perceived standard of the education system, safety, geographic proximity to home, cost of living, overseas programmes being considered as superior to the programmes available in their home country and social influences. However, extant minimal research which has explored motivations for international students choosing to study in developing countries, such as China, has produced conflicting results. To address these aforementioned research gaps, this study aims to provide a detailed understanding of why international students choose China, how they make their decision and their experiences of studying in China. Adopting an exploratory, qualitative approach, semi-structured interviews were conducted with 13 international students from a range of different nationalities. Interviews discussed students’ motivations for choosing China as a study destination, the factors which influenced their decision, and their experiences of studying in China. Thematic analysis was used to analyse and interpret the data to reveal 14 key themes. The findings revealed that university reputation is the most influential factor in international students’ decisions to study in China. Therefore, education quality is of paramount importance to students considering China as a study destination. Economic factors, specifically perceived increased career prospects and China’s rise as an emerging superpower also exerted a strong influence on students’ decisions. Undergraduate students’ decision to study in China was heavily influenced by their parents, particularly for students of Chinese descent, whereas postgraduate students were influenced by their teachers. Scholarships and low cost of tuition played a contributing factor in students decision to choose China as a study destination. Students conducted minimal research prior to deciding to study in China and adopted a “give it a shot” attitude. Nevertheless, they reported their experience of studying in China as positive. The opportunity to overcome the challenges of studying in China is considered advantageous and results in enhanced self-esteem and the creation of a unique identity that differentiates students from their peers who study in more traditional host destinations. This research contributes insight into the multidirectional flow of international education, specifically, international students’ decision to study in China. Contributions towards both theory and practice are provided. A theoretical model describing the factors which motivate international students to choose China as a host destination is presented. Managerial implications and recommendations to assist the Chinese government and universities in achieving their international education goals are provided.
Keywords: Internationalization; Students; Decision making; Higher education; International student mobility; China